Improving methods estimation of the investment climate of the country - E. V. Ryabinin (Statistika i Èkonomika, 2016)
This article discusses the key problems of assessing the country’s investment climate. The subject in the light of recent political events, has received increased attention. For reasons of increasing political tensions between Russia and the West, the investment activity is significantly reduced among foreign investors in our country. Studies have shown that the main problems of the current investment climate assessment methodologies are objectivity, comprehensiveness, relevance and comparability of proposed assessments. This article provides a mechanism for solving the above problems by using a multifactor model of investment attractiveness. The information base for the study served as the official annual statistical reports and bulletins of international organizations such as: IBCA, Moody’s, Standard & Poor’s, Monetary Fund, OPEC, UNCTAD, UNESCO, World bank, etc. The key theoretical positions on the assessment of the investment climate in the country were presented the results of the analysis reports and reviews of the international consulting company Ernst and Young and Deloitte, the official Internet resource of Russian and international business publications: Euromoney, Fortune, The Economist, The Financial Times, BBC, Bloomberg, RBC, Vedomosti and Komersant. The reliability and validity of scientific statements, conclusions and recommendations contained in this article provides the correct use of sufficient analytical and statistical information on the directions of research. In this article, the key attention is paid to the method of mathematical modeling and forecasting. With the introduction of the multiplicative model, where the multipliers are the separately calculated factors and potential risk factors, it is planned to bring the most accurate and objective evaluation model of investment climate in the country. The results articles as data and mathematical models will allow foreign investors to use the most objective assessment of the investment climate in the country in order to build their strategies market functioning. The article describes two methods to obtain an estimate of the investment climate, a fundamental and expertise. Studies have shown that the fundamental method provides the most accurate and objective assessment of, but not all of the investment potential factors can be subjected to mathematical evaluation. The use of expert opinion on the practice of subjectivity difficult to experts, so its use requires special care. In modern economic practice it proved that the investment climate elements directly affect the investment decisions of companies. Improving the investment climate assessment methodology, it allows you to build the most optimal form of cooperation between investors from the host country. In today’s political tensions, this path requires clear cooperation of subjects, both in the domestic and international level. However, now, these measures will avoid the destabilization of Russia’s relations with foreign investors.